2019
DOI: 10.1016/j.nima.2018.06.073
|View full text |Cite
|
Sign up to set email alerts
|

X-ray response evaluation in subpixel level for X-ray SOI pixel detectors

Abstract: We have been developing event-driven SOI Pixel Detectors, named "XRPIX" (X-Ray soiPIXel) based on the silicon-on-insulator (SOI) pixel technology, for the future X-ray astronomical satellite with wide band coverage from 0.5 keV to 40 keV. XRPIX has event trigger output function at each pixel to acquire a good time resolution of a few µs and has Correlated Double Sampling function to reduce electric noises. The good time resolution enables the XRPIX to reduce Non X-ray Background in the high energy band above 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Charge collection efficiency (CCE) should be high enough to achieve superior spectral performance. We irradiated XR-PIX1b and XRPIX3b with an X-ray pencil beam, and found that the CCE becomes lower when X-rays are absorbed near the pixel boundaries [11], [12]. Comparing the experimental data with results from device simulations that we carried out, we came to a conclusion that a part of signal charge is lost due to traps located close to the interface between the sensor and SiO 2 layers [11].…”
Section: A Interference and Charge Collection Efficiency In Xrpixmentioning
confidence: 88%
“…Charge collection efficiency (CCE) should be high enough to achieve superior spectral performance. We irradiated XR-PIX1b and XRPIX3b with an X-ray pencil beam, and found that the CCE becomes lower when X-rays are absorbed near the pixel boundaries [11], [12]. Comparing the experimental data with results from device simulations that we carried out, we came to a conclusion that a part of signal charge is lost due to traps located close to the interface between the sensor and SiO 2 layers [11].…”
Section: A Interference and Charge Collection Efficiency In Xrpixmentioning
confidence: 88%
“…sensors have been reported [16,6,7]. Also, the disruption and/or weakening of the electric field near the pixel edges, which enhances the charge cloud diffusion, has been discussed [5].…”
Section: Hit Position Energy Depositmentioning
confidence: 99%
“…The detector response of the XRPIX sensors has been investigated in several works. Matsumura et al (2015) [5] and Negishi et al (2019) [6] studied the spatial distribution of the charge collection efficiency (CCE) and an electric field structure in the sensors in order to evaluate the XRPIX sensor performance. Hagino et al (2019) [7] modeled the charge cloud size and verified it by comparing it to measured number fractions of chargesharing events.…”
Section: Introductionmentioning
confidence: 99%
“…Here the "effective" thickness is the one measured with X-ray detection and is often different from the one defined in terms of semiconductor processes. So far, we have achieved a performance of detection of 2.1 keV Xrays and an effective thickness of 0.9-1 µm in the Frame readout mode [7,8]. However, the required threshold of 1 keV has not been reached yet.…”
Section: Introductionmentioning
confidence: 99%